PENGARUH FINANCIAL STABILITY, EFEKTIVITAS INTERNAL CONTROL, DAN AUDITOR CHANGE (FRAUD TRIANGLE) TERHADAP FINANCIAL STATEMENT FRAUD - Mayasari Mayasari; Niken Wulandari (Universitas Prof. Dr. Moestopo (Beragama), 2022)
This study aims to find out the effects of financial stability, internal control effectiveness, and auditor change on financial statement fraud. Where in this research population are food sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2017-2022. The method of determining the sample is done by purposive sampling technique. The data obtained for 21 companies from 2017 to 2020 was associated with 4 research variables, namely 3 independent variables: financial stability, internal control effectiveness, and auditor change and 1 dependent variable: financial statement fraud. The analysis in this study uses logistic regression analysis. In this study using descriptive statistical tests, variable in the equation tests, iteration history tests, Hosmer and Lemeshow tests, model summary tests, and classification tables that will occur this study shares that (1) Financial stability has a significant positive effect on financial statement fraud . (2) The effectiveness of Internal Control has a positive but not significant effect on the Fraud Financial Statement variable. (3) Auditor Change has a positive but not significant effect on the Fraud Financial Statement variable. (4) What will happen from the sample summary test states that 14.3 percent of fraudulent financial reporting is influenced by the three research variables, while the remaining 85.7 percent is influenced by other variables not explained in this study.